The Impact of Social Interaction for the Result of Social Subject Grade VII in UPTD SMP Negeri 1 Pematang Siantar - Briant Sunggul Pakpahan (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the "Influence of Social Interaction on Student Learning Outcomes in Social Sciences Subjects Class VIII UPTD SMP Negeri 1 Pematang Siantar". This type of research is quantitative research with a quantitative descriptive analysis approach. The research population was students at the UPTD SMP Negeri 1 Pematang Siantar school with a total of 187 students. The sampling technique used was the Slovin sampling technique. Data collection techniques use questionnaires, tests and documentation. The hypothesis generation technique uses simple linear regression analysis and the coefficient of determination (R2). The results of the research show that: there is a positive and significant influence on social interaction on student learning outcomes. This result can be seen in the t test where the calculated t value of social interaction (9.995) > t table value (2.6025) which means the variable is significant. The R Square coefficient of determination test was found to be 0.35, which means that 35% of social interaction variables influence student learning outcomes at the UPTD SMP Negeri 1 Pematang Siantar school. Meanwhile, 65% is the influence of other variables not examined in this research. Y : 10.127 + 0.778